(3GdUMjaI aj GdJLQHI GdUMjMIs - (3aNQ GdOhdI CHh TGcQ Hf jYbhH GdfUQGfis; (3eMeO Hf Gejd Hf YHO Gddg Hf Gejd (B( (3GSO (B)(3GdJejej,J (B170 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI (B: (3hPcQ GdeDda (B: (3LQJ YGOI Gdbhe Cf jLgdhG gPg GdUfGYI ef cd WGdH s
(3BNQgG (B:s
(3hGdMeO ddg Ydi GdEMSGf hGdMeO dhdi GdMeO hefg GdQMeI hUdi Gddg Ydi SjOfG eMeO hBdg CLejYf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B32 - (3U(B33s
(3GdfSNI HgG MhGTs
(3QSGdI GdTeS Edi GdgdGd deG HOCJ ai QbI GdNdGds
(3hgPg GdQSGdI JSei (B" (3eNeS GdeGA GdhQbi hGdCQV GdfLejI (B" (3ceG JSei(B" (3eHJOC GdEQSGd (B" "(3QSGdI GdTeS Edi GdgdGd (B" (3heWdYgGs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs